2009
DOI: 10.1128/aem.01931-08
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Experimental Choices and Analysis Noise on Surveys of the “Rare Biosphere”

Abstract: When planning a survey of 16S rRNA genes from a complex environment, investigators face many choices including which primers to use and how to taxonomically classify sequences. In this study, we explored how these choices affected a survey of microbial diversity in a sample taken from the aerobic basin of the activated sludge of a North Carolina wastewater treatment plant. We performed pyrosequencing reactions on PCR products generated from primers targeting the V1-V2, V6, and V6-V7 variable regions of the 16S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…msu.edu/probematch/search.jsp) revealed that the reverse PCR primer (806R) targets cyanobacteria very poorly (matching o1% known cyanobacterial sequences). Although PCR primer-related biases are well known, some reports suggested that it is largely limited to 'rare' taxa (Huse et al, 2008;Hamp et al, 2009). Here we demonstrate a case where PCR primer bias can influence observed diversity at the phylum level.…”
Section: Discussionmentioning
confidence: 99%
“…msu.edu/probematch/search.jsp) revealed that the reverse PCR primer (806R) targets cyanobacteria very poorly (matching o1% known cyanobacterial sequences). Although PCR primer-related biases are well known, some reports suggested that it is largely limited to 'rare' taxa (Huse et al, 2008;Hamp et al, 2009). Here we demonstrate a case where PCR primer bias can influence observed diversity at the phylum level.…”
Section: Discussionmentioning
confidence: 99%
“…Pyrosequencing errors have been reported to cause significantly inflated estimates of microbial species, particularly for rare biospheres (Quince et al, 2009;Reeder and Knight, 2009). Currently, PCR biases, sequencing errors and bioinformatics pipelines are the three major hurdles to the accurate assessment of microbial diversity (Hamp et al, 2009;Huber et al, 2009;Huse et al, 2010;Kunin et al, 2010). Our study encompassed both PCR and sequencing errors, but we believe that the sequencing errors were minimized.…”
Section: Discussionmentioning
confidence: 99%
“…Extracted RNA was reverse transcribed into cDNA using SuperScript VILO (Invitrogen). A portion of the 16S small subunit ribosomal gene was amplified from DNA or cDNA using the 27F (5Ј-AGAGT TTGATCCTGGCTCAG-3Ј) primer with the Roche 454 "A" pyrosequencing adapter (5Ј-GCCTCCCTCGCGCCATCAG-3Ј) and a 4-bp barcode sequence and the 337R (5Ј-GCTGCCTCCCGTAGGAGT-3Ј) primer (19) containing the Roche 454 "B" sequencing adapter (5Ј-GCCTTGCCAGCCCGCTCAG-3Ј). The unique 4-bp barcode was included on the forward primer for sorting pooled DNA-and RNA-derived data sets.…”
Section: Methodsmentioning
confidence: 99%